Attitudes and perceptions of Christian Ministers of Iloilo City on the Estrada impeachment case - Armada, Melvin; Corvera, April Joy; de la Peña, Francis; Jarana, Rhona; Olandia, Sherry Lei
In a country whose population is predominantly Christian, the opinions and views of religious officials, Catholic or otherwise are a great source of insight. Religious officials have different views on the intricacies of the word of God. But on some issues their perception and attitudes possess homogeneity. This uncanny phenomenn may be explained in part by the fact that all religious officials especially the Christian ministers base their opinions and have for a guide the Holy Bible, with a common sequence to guide their actions. Also, they may be part of an organization, but mostly these organizations have no political affiliation, thus encouraging a non-bias political stand. We, the researchers pound them to a very viable and interesting group to conduct our study with. One of the most significant requisites for any study is its relevance. Especially if the issue being tackled is significant, timely and encompassing such as the President's impeachment trial. This is one way of finding out where are the Christian Ministers in light of the political crisis that confront the country. This particular study aims to extract the perspective and feelings of Christian Ministers in Iloilo City about the impeachment proceedings and to find out the varying degree of stand in this issue that is political in nature.